Lattice Boltzmann Model for Simulation of Avalanche Formation and Streamer Discharge in Breakdown of Gaseous Dielectrics - Wang, Nan; Lei, Qingquan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Gas discharges play a central role in the electrical breakdown of matter, both in nature and technology. Therefore, accurate modeling and simulation of streamers in gaseous discharge processes are of particular interest. This study presents the formulation of computationally efficient models of the charge density and electric field produced by the lattice Boltzmann method. The propagation of double-headed streamers is described in 1-cm plane-to-plane geometry in pure nitrogen at atmospheric pressure by 1.5D and 2D models. The lattice Boltzmann method was successfully applied to the simulation of streamer discharges. Therefore, this scheme is a potential way of simulating gaseous discharge problems.